Aplikasi Pengenalan Rumah Adat Berbasis Augmented Reality Pada Perangkat Mobile Android - Ramzy, Arib Naufal; Fachrie, Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Indonesia has an extraordinary cultural wealth, including various traditional houses reflecting history and values. However, people's understanding of conventional houses is often limited. Factors such as the availability of introductory media and changes in people's mindsets have caused reduced interest and attention to traditional cultural heritage, including traditional houses. Augmented Reality (AR) technology has emerged as an innovative solution to facing this challenge. This research develops an AR-based traditional house introduction application on the Android platform, with the addition of interactive features such as quizzes and puzzles. The research results show that this application can increase people's understanding and interest in Indonesia's cultural heritage. Functionality testing on the Poco F5 and Samsung A50 devices shows valid results, meaning the test is reliable and can provide an accurate picture. Meanwhile, feasibility testing with 7 Yogyakarta Technology University students showed varying responses, but the majority positively assessed this application. By utilizing AR technology, this application can be an essential first step in maintaining and promoting Indonesia's cultural diversity in the digital era.